Posttranscriptional regulation of T-type Ca2+ channel expression by interleukin-6 in prostate cancer cells. Issue 2 (December 2015) - Weaver, Erika M.; Zamora, Francis J.; Hearne, Jennifer L.; Martin-Caraballo, Miguel
Highlights: IL-6 evoked T-type Ca 2+ channel expression was examined in prostate cancer cells. IL-6 has no effect on Cav 3.2 mRNA, but increases Cav 3.2 protein expression. IL-6 effect on the expression of functional channels in the membrane was minimal. IL-6 and forskolin promotes the functional expression of T-type Ca 2+ channels. Functional T-type Ca 2+ channels regulate morphological cell differentiation. Abstract: Background: At early stages, the growth of prostate cancers is androgen dependent. At later stages, however, the growth of prostate cancers becomes androgen independent, which leads to an increase in mortality. The switch to an androgen-refractory state is associated with neuroendocrine differentiation (NED) of prostate cancer cells. Several factors including interleukin-6 (IL-6) and increased cAMP production promote NED of prostate cancer cells. In this work we investigated whether IL-6 evoked NED of LNCaP cells results in a significant change in T-type Ca 2+ channel expression in comparison to non-stimulated LNCaP cells. Methods: T-type Ca 2+ channel subunit Cav 3.2 expression was studied using PCR analysis, western blot and whole cell recordings. Tubulin IIIβ expression and neurite-like morphology was assessed to investigate the role of T-type Ca 2+ channels in the differentiation of prostate cancer cells. Results: Treatment of LNCaP cells with IL-6 for 4 days evokes considerable morphological and biochemical changes consistent with NED. Transcripts of the T-type Ca 2+ channel subunit Cav 3.2 but not Cav 3.1 or Cav 3.3 are detected in IL-6 stimulated cells. Real time PCR analysis of IL-6 stimulated cells indicates no significant change in Cav 3.2 mRNA expression in comparison to non-stimulated cells. LNCaP cells stimulated with IL-6 show a threefold increase in T-type Ca 2+ channel subunit Cav 3.2 protein expression, suggesting that channel expression is upregulated by a posttranscriptional mechanism. Electrophysiological recordings reveal that increased Cav 3.2 protein expression following IL-6 stimulation of LNCaP cells does not result in increased expression of functional channels in the membrane. Functional expression of Cav 3.2 channels in LNCaP cells is facilitated by co-stimulation with IL-6 and the cAMP-stimulating agent, forskolin (FSK). Inhibition of T-type Ca 2+ channel activity in IL-6 stimulated LNCaP cells prevents the development of morphological characteristics consistent with NED. Conclusions: These results indicate that the functional expression of T-type Ca 2+ channels is regulated by the interplay of multiple factors in LNCaP cells.